(untitled) (CIPEEX, 2025)
Objective: To describe the number of cases, sociodemographic data involved, and causes of maternal mortality in the state of Goiás between 2017 and 2021. Methods: This is an ecological, descriptive, quantitative study, based on the secondary analysis of data, covering the period from 2017 to 2021, using information from the Department of Informatics of the Unified Health System (DATASUS). Results: The present study described risks and vulnerabilities related to maternal mortality in Goiás, as well as the main causes, observing an upward curve in relation to the number of deaths and various associated epidemiological profiles, especially from the year 2020. In addition, the main causes of maternal death were described according to ICD-10, providing greater knowledge on the subject. Conclusion: It was concluded that social inequalities are related to the increase in maternal mortality cases in the state of Goiás and that further investigation of the causes is necessary, especially those recorded by ICD-10, so that the upward curve of maternal mortality does not persist, enabling specific interventions in cases of complications.